2019
DOI: 10.14744/ijmb.2019.47965
|View full text |Cite
|
Sign up to set email alerts
|

S100B and Latent Toxoplasmosis in Alzheimer’s disease

Abstract: A lzheimer's disease (AD) is a fatal neurodegenerative disorder characterized by progressive neuronal loss and loss of cognitive function. AD is the most common type of dementia and its prevalence is approximately 10% after 90 years of age [1]. The number of cases worldwide in 2005 was 47 million and it is expected to be 131 million in the year 2050 [2]. Although neuronal loss and brain dysfunction is well known in AD, its pathogenic mechanism is not fully clear. Studies in the literature have focused on 3 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…To the best of our knowledge, this is the first study exploring the effects of T. gondii infection on biomarkers in TBI. However, Ayyildiz et al [43] studied S100B serum levels associated with T. gondii positivity in Alzheimer disease, and found no significant variation in the levels of serum S100B between T. gondii-positive and -negative Alzheimer patients. This variation in results may be due to the fact that their sample size was small (33) or simply to a difference in the underlying pathology, e.g., chronic versus acute.…”
Section: Concentrations Of the Biomarkers According To Toxoplasma Gon...mentioning
confidence: 99%
“…To the best of our knowledge, this is the first study exploring the effects of T. gondii infection on biomarkers in TBI. However, Ayyildiz et al [43] studied S100B serum levels associated with T. gondii positivity in Alzheimer disease, and found no significant variation in the levels of serum S100B between T. gondii-positive and -negative Alzheimer patients. This variation in results may be due to the fact that their sample size was small (33) or simply to a difference in the underlying pathology, e.g., chronic versus acute.…”
Section: Concentrations Of the Biomarkers According To Toxoplasma Gon...mentioning
confidence: 99%
“…Another study in a murine of Alzheimer's disease suggested that Toxoplasma infection of brain can inhibit neuronal degeneration and memory and learning impairments [26]. The infection may modulate the immune system and affect the balance of neurotransmitters, such as dopamine, serotonin and glutamate, which may influence the mood, behaviour and cognition of individuals with Alzheimer's disease [45, 50]. LT may increase the risk of dementia by affecting the development of the brain during foetal or early childhood stages [45].…”
Section: Immunological Neurological Psychological and Behavioural Eff...mentioning
confidence: 99%
“…gondii is considered to be among the most resistant intracellular parasites but is thought to remain asymptomatic in most cases. However, recent human studies have implicated toxoplasmosis as a hidden contributor to various forms of dementia [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%